2015
DOI: 10.1111/jpn.12294
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of uniformity of calcium absorption in adult dogs and cats

Abstract: SummaryA meta-analysis was conducted to understand quantitative aspects of calcium (Ca) and phosphorus (P) absorption in adult dogs and cats. 34 studies in dogs and 14 studies in cats met the criteria for inclusion in the meta-analysis. Intake and faecal excretion values of Ca and P were subjected to a modified Lucas test and subsequent regression analyses. According to the current scientific consensus, Ca true digestibility (absorption) should increase at low Ca intake and decrease at high Ca intake. If true,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 34 publications
4
52
2
5
Order By: Relevance
“…Given the differences in calcium requirements of dogs and humans, the relatively common occurrence of clinical calcium deficiency in dogs but not in man, and the outcome of the meta‐analysis of Mack et al. (), we hypothesise that dogs will not effectively increase calcium absorption from the gastrointestinal tract when challenged with a low dietary calcium intake. The National Research Council (NRC) () defines the minimal requirements of a nutrient as requirement of bioavailable nutrient.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given the differences in calcium requirements of dogs and humans, the relatively common occurrence of clinical calcium deficiency in dogs but not in man, and the outcome of the meta‐analysis of Mack et al. (), we hypothesise that dogs will not effectively increase calcium absorption from the gastrointestinal tract when challenged with a low dietary calcium intake. The National Research Council (NRC) () defines the minimal requirements of a nutrient as requirement of bioavailable nutrient.…”
Section: Introductionmentioning
confidence: 97%
“…A previous meta‐analysis of digestion trials in dogs suggested that true digestibility of calcium does not notably increase when calcium intake is below requirements (Mack, Alexander, Morris, Dobenecker, & Kienzle, ). Given the differences in calcium requirements of dogs and humans, the relatively common occurrence of clinical calcium deficiency in dogs but not in man, and the outcome of the meta‐analysis of Mack et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta‐analysis on calcium (Ca) and phosphorus (P) intake vs. faecal excretion in dogs and cats, Mack, Alexander, Morris, Dobenecker, and Kienzle () observed a close linear relationship between faecal Ca and P excretion ( R ² = .94 in dogs), regardless of the Ca/P ratio and the source of Ca and P in the food. A possible explanation could be the formation of insoluble Ca/P complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The NRC discusses many uncertainties in the bioavailability of Ca in dogs ( 3 ) . A recent meta-analysis ( 4 ) plotted literature data on Ca intake against faecal Ca excretion in adult dogs in a modified Lukas test. The relationship between intake and faecal excretion showed a remarkable uniformity, a result which does not suggest a pronounced high variability of Ca availability.…”
mentioning
confidence: 99%